Mobilizing Pedagogy Two Social Practice Projects in the Americas by Pablo Helguera with Suzanne Lacy and Pilar Riaño-Alcalá - Gonzales, Elyse A.; Reisman, Sara (Amherst College Press, 2018)
What is-what should be-the place of art in society? Is it merely decorative? Is it only to affirm a given set of cultural preferences? Or should it examine, challenge, even upend these norms to bring open new perspectives for those who experience what artists create? Social practice artists offer a clear and unflinching answer to this question, setting before us works intended not merely to ask questions but to propose pathways toward large societal change. In this volume, the work of two social practice artists of different generations and different social locations-Suzanne Lacy and Pablo Helguera-are brought into creative tension by two visionary curators: Elyse A. Gonzalez of the Art, Design & Architecture Museum of the University of California, Santa Barbara, and Sara Reisman of the Shelley and Donald Rubin Foundation of New York. Working together, Gonzales and Reisman bring the work of these two engaged and activist artists into dialogue, showing how art can be not merely the mirror of society but the means of making it more just, more inclusive, and more humane.